An oxygen cathode with stable full discharge–charge capability based on 2D conducting oxide1. Issue 7 (1st July 2015) - Liao, Kaiming; Wang, Xuebin; Sun, Yang; Tang, Daiming; Han, Min; He, Ping; Jiang, Xiangfen; Zhang, Tao; Zhou, Haoshen
<x xml:space="preserve">Abstract</x> Two-dimensional conducting oxide (RuO2) nanosheet cathode enables Li–O2 batteries to be operated 50 cycles under full discharge–charge conditions with a specific capacity of ∼900 mAh g−1.